2022
DOI: 10.3390/s22103867
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sensor Placement for Modal-Based Health Monitoring of a Composite Structure

Abstract: Optimal sensor placement is one of the important issues in monitoring the condition of structures, which has a major influence on monitoring system performance and cost. Due to this, it is still an open problem to find a compromise between these two parameters. In this study, the problem of optimal sensor placement was investigated for a composite plate with simulated internal damage. To solve this problem, different sensor placement methods with different constraint variants were applied. The advantage of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 56 publications
(103 reference statements)
0
45
0
Order By: Relevance
“…The number of sensors and their location can be specified as the design parameters taking into account various constraints, which may include the boundary conditions, sensor sizes, etc. This method was tested on a composite plate and demonstrated good results [32].…”
Section: Optimal Sensor Placement Methodsmentioning
confidence: 99%
“…The number of sensors and their location can be specified as the design parameters taking into account various constraints, which may include the boundary conditions, sensor sizes, etc. This method was tested on a composite plate and demonstrated good results [32].…”
Section: Optimal Sensor Placement Methodsmentioning
confidence: 99%
“…Systematic studies on the detection of delamination in PMCs using the optimized sensor network demonstrated satisfactory results. The novel data-driven experimental approach proposed in this study, which was an improvement to previous computational results [ 15 ], is robust to measurement noise and reveals a high effectiveness in damage detection due to the applied combination of both numerical and experimental results in the learning algorithm. The developed data-driven approach falls into the current trends in the development of SHM systems, a concept which was recently used, e.g., by the authors of [ 23 ].…”
Section: Introductionmentioning
confidence: 92%
“…As discussed in our previous study [ 15 ], the oldest and most widespread SHM approach is based on monitoring the vibration response of a structure, which is considered in many applications, including composite beams [ 16 ] and plates [ 17 , 18 , 19 ]. An overview of the variety of approaches to the problem of optimal sensor placement (OSP) in vibration-based SHM presented in [ 15 ] clearly shows the necessity of developing effective algorithms focused on minimizing the number of sensors in the measurement network without losing the quality and accuracy of structural damage. The fundamentality of solving an OSP problem in SHM systems is underlined in many recent studies; see, e.g., [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations